THE EFFECT OF PROFITABILITY, COMPANY SIZE, AND CAPITAL INTENSITY ON TAX AGGRESSIVENESS WITH INDEPENDENT COMMISSIONERS AS A MODERATING VARIABLE - Hadid Prastyo, Fatah; Pramono Sari, Maylia; Ekaviana, Dessy (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
The purpose of this study was to analyze the effect of profitability, company size, and capital intensity on tax aggressiveness with independent commissioners as a moderation variable. The population in this study is the consumption sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022. Samples were taken using non-probability techniques with purposive sampling method and obtained as many as 219 units of analysis. The results of this study is a positive effect but not significant profitability of tax aggressiveness. While the size of the company has a positive and significant effect on tax aggressiveness. Then capital intensity has a negative and significant effect on tax aggressiveness. Independent commissioners are not able to weaken the effect of profitability on tax aggressiveness, but independent commissioners are able to weaken the effect of company size and capital intensity on tax aggressiveness.